Sustainable pectin extraction from Riang husk using ultrasound-assisted extraction with deep eutectic solvents and its potential in antipollution products - Manee Saelee; Hla Myo; Nuntawat Khat-udomkiri (Ultrasonics Sonochemistry)
With increasing concerns about air pollution and its adverse effects on health, particularly in Thailand, the demand for antipollution products has risen significantly. Parkia timoriana (DC.) Merr., commonly known as Riang, has emerged as a promising source for developing antipollution products due to its characteristics. This study investigates the use of ultrasound-assisted extraction (UAE) combined with deep eutectic solvents (DESs) as a sustainable and efficient method for optimizing pectin extraction from Riang husks through the evaluation of a central composite design (CCD), and the structural, functional, and rheological characteristics of the extracted pectin. The antioxidant activity and protective effects against PM2.5-induced cellular damage of this method were also evaluated. The condition that exhibited the highest yield were found to be a liquid-to-solid ratio of 40 mL/g, 35 % amplitude (ultrasonic power of 28.11 W), and 60 min of extraction time. The extracted pectin was primarily composed of monosaccharides, including galacturonic acid (53.74 %), arabinose (23.97 %), galactose (12.36 %), and rhamnose (6.81 %). The degree of esterification (DE) was 73.41 %, classifying it as high methoxyl pectin. Functionally, the pectin demonstrated a solubility of 53 %, a water holding capacity of 3.88 g water/g pectin, an oil holding capacity of 3.30 g oil/g pectin, and a swelling capacity of 11.77 mL/g. Rheological analysis showed shear-thinning behavior across all pH gel forms. Furthermore, Riang husk pectin exhibited antioxidant activity, measured at 0.26 ± 0.02 mmol Trolox equivalents/g, and demonstrated cytoprotective effects against hydrogen peroxide-induced oxidative stress. It also attenuated damage caused by PM2.5 in HaCaT cells. The current study highlights UAE combined with DESs as a sustainable and effective method for obtaining high-quality pectin, contributing to the development of antipollution products and supporting sustainability goals.